Blood meal analysis of tabanid fly after it biting the rare Sumatran rhinoceros - Jeffrine Japning, Rovie-Ryan; Zainal Zahari, Zainuddin; Wahap, Marni; Abdul Hamid, Ahmad; Laurentius N., Ambu; Junaidi, Payne (Asian Pacific Journal of Tropical Biomedicine, 2013)
Objective:To demonstrate a noninvasive large mammalian genetic sampling method using blood meal obtained from a tabanid fly. Methods:Blood meal was recovered from the abdomen of an engorged tabanid fly(Haemotopota sp.) which was captured immediately after biting a Sumatran rhino in captivity.the blood was applied on to a Whatman FTA blood card. Subsequent laboratory work was conducted to extract,amplify and sequence the DNA from the sample. Validation was done by sampling the hair follicles and blood samples from the rhinocheros and subjecting it to the same laboratory process. Results:BLAST search and constructed phylogenetic trees confirmed the blood meal samples were indeed from rhino. Conclusions: This method could be used in the field application to noninvasively collect genetics samples. Collection of tabanids and other haematophagous artropods(e.g.mosquitoes and ticks) and other blood-sucking parasites (e.g. leeches and worms) could also provide information on vector-borne diseases.